Molecular detection of bla CTX-M gene to predict phenotypic cephalosporin resistance and clinical outcome of Escherichia coli bloodstream infections in Vietnam - Trinh Van Son; Nguyen Dang Manh; Ngo Tat Trung; Dao Thanh Quyen; Christian G. Meyer; Nguyen Thi Kim Phuong; Phan Quoc Hoan; Vu Viet Sang; Dennis Nurjadi; Thirumalaisamy P. Velavan; Mai Hong Bang; Le Huu Song (BMC, 2021)
Abstract Background Blood stream infections (BSI) caused by Extended Spectrum Beta-Lactamases (ESBLs) producing Enterobacteriaceae is a clinical challenge leading to high mortality, especially in developing countries. In this study, we sought to describe the epidemiology of ESBL-producing Escherichia coli strains isolated from Vietnamese individuals with BSI, to investigate the concordance of genotypic-phenotypic resistance, and clinical outcome of ESBL E. coli BSI. Methods A total of 459 hospitalized patients with BSI were screened between October 2014 and May 2016. 115 E. coli strains from 115 BSI patients were isolated and tested for antibiotic resistance using the VITEK®2 system. The ESBL phenotype was determined by double disk diffusion method following the guideline of Clinical and Laboratory Standards Institute. Screening for beta-lactamase (ESBL and carbapenemase) genes was performed using a multiplex-PCR assay. Results 58% (67/115) of the E. coli strains were ESBL-producers and all were susceptible to both imipenem and meropenem. Resistance to third-generation cephalosporin was common, 70% (81/115) were cefotaxime-resistant and 45% (52/115) were ceftazidime-resistant. bla CTX-M was the most common ESBL gene detected (70%; 80/115) The sensitivity and specificity of bla CTX-M-detection to predict the ESBL phenotype was 87% (76-93% 95% CI) and 54% (39-48% 95% CI), respectively. 28%% (22/80) of bla CTX-M were classified as non-ESBL producers by phenotypic testing for ESBL production. The detection of bla CTX-M in ESBL-negative E. coli BSI was associated with fatal clinical outcome (27%; 6/22 versus 8%; 2/26, p = 0.07). Conclusion A high prevalence of ESBL-producing E. coli isolates harbouring bla CTX-M was observed in BSI patients in Vietnam. The genotypic detection of bla CTX-M may have added benefit in optimizing and guiding empirical antibiotic therapy of E. coli BSI to improve clinical outcome.